Host, vector, environment and management: epidemiology of bovine anaplasmosis in the state of Kansas - Spare, Mark Randall (Kansas State University, 2021)
Bovine anaplasmosis was first described in the state of Kansas in 1926. Today, nearly a century later, this disease continues to impact beef cattle health having negative impacts on profitability and creating significant hurdles for genetic improvement in the cattle industry. The characteristics of Anaplasma marginale allow the bacterium to use unique opportunities within different environments to maintain infection presence and evade interventions. Extra-label uses of the antibiotic in animal feeds, including common dosages for the control of anaplasmosis, are illegal. Current management to control anaplasmosis in beef cattle herds is an integrated approach that requires decisions to be made at the individual animal and population herd level. The objectives of this dissertation were to describe the distribution and infection prevalence of the tick vectors and cattle populations at a similar point in time in Kansas to offer baseline information to aid producers and their veterinarians. Another goal of the dissertation was to examine the effects of approved therapeutic regimens on the clinical outcomes in naturally infected cattle in a commercial setting. In the first study, the questing tick vector was collected and identified over a two-year period in the Flint Hills ecoregion of Kansas. The association of the vector with climate data and land cover was modeled using general linear mixed modeling. The results of this study demonstrated significant associations between climate and tick density. In the second study, the infection prevalence of cattle throughout the state was described at the herd level and a survey administered to participating cattle operations. The results of this study demonstrated a widespread, but unequal herd-level infection prevalence across the state which is associated with specific management practices. The final study included in this dissertation was conducted to examine the effects of feeding an approved level of chlortetracycline medicated therapy, with or without supplemental injectable oxytetracycline, to chemosterilize yearling beef bulls naturally infected with anaplasmosis in a commercial feeding situation. The results of the study indicate that the delivery of chlortetracycline for 80 days is insufficient to chemosterilize group fed yearling beef bulls. Injectable oxytetracycline in combination with chlortetracycline also had no effect on the chemosterilization of study cattle. All beef bulls naturally infected with anaplasmosis with lower level of reported inhibition percentage according to competitive enzyme linked immunosorbent assay were chemosterilized within 40 days on chlortetracycline, while no bulls with higher reported inhibition percentages were chemosterilized regardless of treatment. The research encompassed in this dissertation establish new baseline information for the distribution of bovine anaplasmosis within the vector and host populations throughout the state of Kansas. The inability for approved antibiotic therapy in a commercial setting adds to the understanding and expectations for producers and veterinarians for the use of this tool for the control and treatment of anaplasmosis in their herds. Further research is warranted in the prevention, control, and within herd epidemiology to guide future decisions in the management of this vector-borne disease in the state.
Keywords: Anaplasmosis; Beef cattle; Therapy; Epidemiology; Ticks; Vector